Analysis of Factors Attributing to Hepatitis B Vaccine Non-response - Chen, Qiqi (Transactions on Materials, Biotechnology and Life Sciences, 2024)
Currently, 5-15% of hepatitis B vaccine recipients are non-responders despite the high global coverage 83% of the hepatitis B vaccine. The research of hepatitis B vaccine nonresponse had been going on for some time for the improvement of the vaccine and the objective to eliminate hepatitis B, this paper aims to summarize some of the factors contributing to hepatitis B vaccine nonresponse base of these previous studies after scrutiny. Factors contributing to hepatitis B vaccine nonresponse including HLA haplotypes, age, elder with comorbid condition, obesity, smoking, presence of micronutrient deficiency is involved in this paper. The understanding of these factors is important for the further progression of the vaccine, improvements like repeated vaccination, a booster dose, use of immune boosters, vaccine with a higher dosage, a different adjuvant, a more effective antigen, a different administration route of the vaccine, change of needle length when injecting the vaccine can be made considering the nonresponse factors, therefore increasing the efficacy of hepatitis B vaccine.